Sosialisasi Peraturan Sistem Pesawat Udara Kecil Tanpa Awak (SPUKTA) Kepada Personel Keamanan Bandar Udara Dalam Wilayah KKOP Di Bandar Udara Internasional Silangit - Putu Widi Aryani; Muhammad Caesar Akbar; Ivana Wardani; Tiara Sylvia; Erwin Lumban Gaol (Politeknik Penerbangan Indonesia Curug, 2024)
Small uncrewed aircraft have become one of the increasingly popular technological innovations and are widely used in various fields, including civil aviation. However, using drones also carries potential risks to flight safety and airport security, mainly when operating in the Flight Operational Control Area (KKOP) around the airport. Therefore, it is important to conduct effective socialization regarding the Small Unmanned Aircraft System (SPUKTA) regulations for airport security personnel to increase understanding of using small uncrewed aircraft operations for the public and workers.This community service research results show that the socialization of SPUKTA regulations to airport security personnel in the KKOP area at Silangit International Airport is done through training and counseling. Socialization includes an understanding of drone classification, flight restrictions in the KKOP area, licensing procedures, and emergency actions in dealing with drone operational disruptions, as well as detection and barrier technology to prevent the entry of unauthorized drones. Collaboration between aviation authorities, airport management, and security personnel is needed to continuously update and improve the socialization of SPUKTA regulations to maintain the safety and security of flight operations at Silangit International Airport.